Effects of Postprandial Lipemia Combined With Disturbed Blood Flow on the Flow-Mediated Dilation, Oxidative Stress, and Endothelial Microvesicles in Healthy Subjects - Araujo, Gustavo S. M.; Silva, Thiago O. C.; Guerra, Grazia M.; Izaias, João E.; Rocha, Helena M. N.; Faria, Diego; Rocha, Natalia G.; Dalmazo, Aline Lopes; Araujo, Amanda; Marciano Consolim-Colombo, Fernanda; de Angelis, Katia; Irigoyen, Maria C. C.; et al. (Frontiers in Physiology, 2022)
Aims: Both postprandial lipemia (PPL) and disturbed blood flow (DBF) induce endothelial dysfunction. However, the interactive effect of these stimuli on endothelial function is currently unknown. In the present study, we tested whether PPL plus DBF causes a greater reduction in flow-mediated dilation (FMD) than PPL plus normal blood flow (NBF) and if this response is associated with elevations in oxidative stress and endothelial macrovesicles (EMVs). Methods: Eighteen individuals (aged 28±1 yrs, 3 females, and BMI 24.43±0.8 kg/m2) randomly underwent two experimental sessions: PPL plus NBF and PPL plus DBF. FMD and venous blood samples were obtained at baseline and 30, 70, and 110 min after stimulation. PPL was induced by fat overload via mozzarella pizza ingestion and DBF by forearm cuff inflation to 75 mm Hg per 30 min. Lipidic profile, oxidative stress, and EMVs were measured in blood samples. Results: Hypertriglyceridemia was observed in both sessions. Retrograde shear rate and oscillatory index responses were significantly higher in the PPL plus DBF compared with PPL plus NBF. PPL plus DBF evoked a greater reduction in FMD than did PPL plus NBF. EMVs, NADPH oxidase, and H2O2 similarly increased in both sessions, but TBARS and FRAP did not change. Conclusion: These data indicate that the association of PPL plus DBF additively impairs endothelium-dependent function in healthy individuals, despite a similar increase in oxidative stress and EMVs. Further studies are needed to understand the mechanisms associated with the endothelial dysfunction induced by the association of PPL and DBF.